Recent breakthroughs in deep aerobic oxidative desulfurization of petroleum refinery products. (20th April 2021) - Shafiq, Iqrash; Shafique, Sumeer; Akhter, Parveen; Ishaq, Manzar; Yang, Wenshu; Hussain, Murid
Abstract: The production of greener refinery products has the utmost importance in sustaining a healthy environment worldwide. The amputation of refractory organosulfur compounds is a prodigious challenge in the modern era for petroleum refineries. The oxidation of these rigorous organosulfur compounds is dynamic in the course of deep oxidative desulfurization. As a greener, non-toxic and inexpensive oxidant with copious availability, molecular oxygen existing in ambient air has been employed in the deep oxidative desulfurization technology as an alternative to hydrogen peroxide and other carbon-based hydroperoxides in recent years. However, molecular oxygen activation under mild circumstances is still a challenge. This prospective review critically analyzes the recent advances governed for the development of efficient materials for deep aerobic desulfurization system for the removal of refractory organosulfur compounds. Furthermore, the research gaps in the development and commercialization of deep oxidative desulfurization processes have been identified and significant recommendations are proposed to address the forthcoming challenges. Graphical abstract: Image 1 Highlights: ODS is an auspicious technique for sulfur removal from refinery products. Sulfides are oxidized to their corresponding sulfoxides and sulfones. Various aerobic oxidizing systems have been discussed. Effects of the nature of catalyst on ODS performance have been reviewed. Aerobic ODS systems are a promising way for achieving near the zero-sulfur goal.